2018
DOI: 10.1039/c8ra03321h
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of Ruellia tuberosa L. extracts against abnormal expression of hepatic detoxification enzymes in diabetic rats

Abstract: Ruellia tuberosa L. (RTL) has been used as a folk medicine for curing diabetes mellitus in East Asia decades. This study investigated the effect of RTL on hepatic detoxification enzyme expression in diabetic rats. Male Wistar rats were fed a high fat diet (HFD) and intraperitoneally injected with streptozotocin (STZ) to induce diabetes. Subsequently, rats received oral administrations of 100 or 400 mg kg À1 body weight RTL extract, in either water (RTLW) or ethanol (RTLE), once a day for 4 weeks. The real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(49 reference statements)
3
8
0
Order By: Relevance
“…RTL extracts also improve the oral glucose tolerance test in HFD-fed STZ-treated rats, and the findings have demonstrated in our previous study (Chang et al, 2018). HOMA-IR and QUICKI are indexes that used clinically to assess IR in patients with DM.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…RTL extracts also improve the oral glucose tolerance test in HFD-fed STZ-treated rats, and the findings have demonstrated in our previous study (Chang et al, 2018). HOMA-IR and QUICKI are indexes that used clinically to assess IR in patients with DM.…”
Section: Discussionsupporting
confidence: 71%
“…However, both RTLW and RTLE significantly ameliorated serum glucose and insulin levels, suggesting hypoglycemic and hypoinsulinemic abilities in T2DM rats. RTL extracts also improve the oral glucose tolerance test in HFD‐fed STZ‐treated rats, and the findings have demonstrated in our previous study (Chang et al., 2018). HOMA‐IR and QUICKI are indexes that used clinically to assess IR in patients with DM.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin resistance has been proved to cause abnormal regulation of lipolysis in peripheral adipocytes, leading to massive release of FFA into blood (Petersen & Shulman, 2006). Our previous study has revealed that RTLW and RTLE may alleviate hyperglycemia and hyperlipidemia via improving insulin resistance in HFD/STZ‐induced type 2 diabetic rats (Chang et al., 2018; Ko et al., 2019). In the normal condition, hepatic triglyceride of less than 5% is derived from endogenous lipid synthesis in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…The extraction protocol was based on our previous methods, with slight modifications [ 7 , 9 ]. One gram of RTL stems and leaves were extracted with 6 ml distilled water and methanol (1 : 6, w / v ) at 4°C for 72 h and filtered using a cheese cloth.…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies have demonstrated that RTL aqueous or ethanolic extracts can significantly improve glucose uptake in C2C12 myoblasts, alleviate the tumor necrosis factor (TNF)- α -induced IR in skeletal muscles, and ameliorate hyperglycemia, IR indices, and aorta dysfunction in high-fat-diet-fed streptozotocin-induced T2DM rats [ 7 , 8 ]. Additionally, RTL ameliorated abnormal hepatic detoxification, nonalcoholic fatty liver disease, and lipid accumulation in the liver of T2DM rats [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%